A novel study of the impact of supply chain complexity on the bullwhip effect - Mohammed El-Beheiry; Raghda Taha; Tamer Ismail; Yasmin Adel (Journal of Transport and Supply Chain Management)
Background: The coronavirus pandemic exposed global supply chain vulnerabilities, causing fluctuating demand for products. This resulted in the bullwhip effect, which posed a substantial challenge for supply chain management. This study focusses on the analysis of the effect of supply chain configurations and structure on the bullwhip effect.